ASESMEN MULTI REPRESENTASI BERBASIS KETERAMPILAN ABAD KE-21 PADA MATERI GERAK LURUS - Ellianawati, Ellianawati; Mufiatunnikmah, Siti; Setyaningsih, Natalia Erna; Subali, Bambang (Physics Education Research Journal, 2020)
This study aims to determine the quality figures of 21st century-based multi-representation assessments on linear motion material. Type of this research is Research & Development (R&D). Data were analyzed using an assessment validity test by an expert and empirical assessment quality test to obtain quality figures in the form of validity, reliability, level of difficulty, and discrimination power. The results of the preliminary field testing analysis showed 58.33% items were declared valid and 41.67% items were declared invalid. Test items have very high reliability with a value of 0.877. The proportion of the level of difficulty is not ideal, that is equal to 58.33% of questions categorized as difficult and 41.67% of questions categorized as sufficient. The discrimination power of the questions is 8.34% of the questions in a good category, 22.22% are sufficient, 58.33% are bad, and 11.11% are very bad. The result of main field testing, 69.44% items were declared valid and 30.56% items were declared invalid. Test items have high reliability with a value of 0.879. The proportion of the level of difficulty obtained in the main field testing is also not ideal, which is 56% of the difficult category and 44% of the sufficient category. The discrimination power consist of 32% good, 40% were sufficient, and 28% were poor.